1996
DOI: 10.1037/1082-989x.1.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The robustness of test statistics to nonnormality and specification error in confirmatory factor analysis.

Abstract: Monte Carlo computer simulations were used to investigate the performance of three X 2 test statistics in confirmatory factor analysis (CFA). Normal theory maximum likelihood )~2 (ML), Browne's asymptotic distribution free X 2 (ADF), and the Satorra-Bentler rescaled X 2 (SB) were examined under varying conditions of sample size, model specification, and multivariate distribution. For properly specified models, ML and SB showed no evidence of bias under normal distributions across all sample sizes, whereas ADF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

92
2,350
8
90

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 4,049 publications
(2,675 citation statements)
references
References 25 publications
92
2,350
8
90
Order By: Relevance
“…Acceptable model fit was based on published recommendations (Hoyle, 1995;Hu & Bentler, 1999): comparative fit index (CFI) ≥.90, root mean square error of approximation (RMSEA) ≤.05, and standardized root mean residual (SRMR) <.08. To accommodate the non-normal data, the Satorra-Bentler scaled chi-square test of difference was used to compare nested models (Curran, West, & Finch, 1996). The initial three-factor model did not yield an acceptable fit, CFI = .892, RMSEA = .108 (90% confidence interval [CI] = .11-.13), SRMR = .062, and χ 2 (61) = 274.907, P <.01, although it was superior to the two-factor model, Δχ 2 (2) = 44.613, P <.001.…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…Acceptable model fit was based on published recommendations (Hoyle, 1995;Hu & Bentler, 1999): comparative fit index (CFI) ≥.90, root mean square error of approximation (RMSEA) ≤.05, and standardized root mean residual (SRMR) <.08. To accommodate the non-normal data, the Satorra-Bentler scaled chi-square test of difference was used to compare nested models (Curran, West, & Finch, 1996). The initial three-factor model did not yield an acceptable fit, CFI = .892, RMSEA = .108 (90% confidence interval [CI] = .11-.13), SRMR = .062, and χ 2 (61) = 274.907, P <.01, although it was superior to the two-factor model, Δχ 2 (2) = 44.613, P <.001.…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…The critical values of skewness and kurtosis were <2.0 and <7.0, respectively, indicating that the normality assumption was not violated. 37 We used structural equation modeling (SEM) to examine the relations between latent traits related to device quality and effect and the more distal outcomes of social participation and isolation. We tested model fit to the data in several steps.…”
Section: Resultsmentioning
confidence: 99%
“…The risk is to wrongly reject a proper model (type 1 error) [45]. We used the SB estimation due to questionable normality of section B in particular.…”
Section: Discussionmentioning
confidence: 99%
“…We used the SB estimation due to questionable normality of section B in particular. The asymptotic distribution free method is applicable for non-continuous data, but was not applied as it may reject properly specified models if sample sizes are small (N < 500) or deviation from normality is minimal [45]. It has been suggested that non-normality is not problematic for the maximum likelihood method until univariate skewness and kurtosis approach 2.0 and 10.0, respectively [45]; our data is below these limits (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation